Occurrence of Salmonella spp. and Campylobacter spp. in exotic birds in Wetland, Putrajaya - Ibrahim, Muhammad Ashraf (2015)
Man and nature, side by side. That is the best words to describe Putrajaya Wetlands the first constructed freshwater wetland and the largest in the tropics. Nevertheless, Putrajaya Wetlands is much more than just an efficient water filter. It has become to some extent the real thing, a functioning wetland, a site with available water to varied exotic bird species and wildlife. However, the exotic birds as carrier of a number of pathogen may have possible zoonotic risk. Therefore, this study was carried out to examine the presence and antibiotic resistance of Salmonella spp. and Campylobacter spp. in exotic birds. Cloaca swab sample was taken from 50 apparently healthy birds from four compartment in quarantine areas, one flamingo pond and one view deck areas. There is no Salmonella spp. was isolated out of 50 samples which were from water birds species which included Black swan, Egyptian goose, Radjah shelduck, Greater flamingo, White pelican, Pink backed pelican and White swan. Campylobacter coli was isolated from 7 (14.0 %) out of 50 cloaca swabs samples from Black Swan, White Pelican and White Swan. Campylobacter lari was isolated from 2(4.0 %) out of 50 cloaca swabs samples from Black Swan only. There was no antibiotic sensitivity test were done on Salmonella spp. because there are no isolated colonies growth. Campylobacter coli and Campylobacter lari isolates were resistance to clindamycin (100%) and sensitive to gentamycin (100%). 55.5% isolates were resistant to one antibiotics while 22% were resistant to 2 antibiotics and there are no resistance to 3 antibiotics. However, there are 22.2% isolates resistant to four antibiotics, which indicate that there is high level of MDR from Campylobacter spp. isolated from exotic birds in Wetland, Putrajaya.